MEMBANGUN KECAKAPAN PENDIDIKAN ISLAM DALAM ERA REVOLUSI INDUSTRI 4.0 - Wahid, Annisa; Hasyim, Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The fourth industrial revolution has transformed the educational landscape, including Islamic education. In this era, the rapid development of information and communication technology has significantly impacted the way we learn and teach. This research aims to explore efforts that can be undertaken to build Islamic education skills in the era of the Fourth Industrial Revolution. This method ushed is library reasearch. Using a qualitative approach, this study involves literature analysis. The findings indicate that there are several key aspects that need to be considered in building Islamic education skills in the era of the Fourth Industrial Revolution. Firstly, the integration of technology in Islamic learning is crucial. The use of software, applications, and online platforms can enhance the effectiveness and efficiency of the learning process. Furthermore, emphasis should be placed on the development of 21st-century skills such as problem-solving, creativity, critical thinking, and collaboration. These skills will enable Islamic students to become competent individuals ready to face global challenges. Additionally, character education should also be a focus in building Islamic education skills. Teaching Islamic values such as integrity, sincerity, justice, and empathy should be reinforced to shape a quality Islamic generation. Collaboration between Islamic educational institutions, teachers, parents, and the community is vital. Through strong synergy, Islamic education can create a holistic learning environment that supports the comprehensive development of students.